Considerações gerais sobre a abordagem e a avaliação da linguagem - Pinto, Maria da Graça Lisboa Castro (1988)
The A. considers the evaluation of language skills and approaches to language assessment, with reference to those variables which are concerned with the collection of data. After having considered longitudinal and transversal perspectives, as well as nomothetic and idiographic approaches, the A. goes on to discuss methodologies concerned with language assessment. The A. concludes that a combination of methodologies is desirable.